Intestinal Mucosal Immunity-Mediated Modulation of the Gut Microbiome by Oral Delivery of Enterococcus faecium Against Salmonella Enteritidis Pathogenesis in a Laying Hen Model - Huang, Shimeng; Rong, Xiaoping; Liu, Meiling; Liang, Zhongjun; Geng, Yanqiang; Wang, Xinyue; Zhang, Jianyun; Ji, Cheng; Zhao, Lihong; Ma, Qiugang (Frontiers in Immunology, 2022)
Enterococcus faecium (E. faecium) is a protective role that has crucial beneficial functions on intestinal homeostasis. This study aimed to investigate the effects of E. faecium on the laying performance, egg quality, host metabolism, intestinal mucosal immunity, and gut microbiota of laying hens under Salmonella enteritidis (S. Enteritidis) challenge. A total of 400 45-week-old laying hens were randomly divided into four treatments (CON, EF, SCON, and SEF groups) with five replicates for each group and 20 hens per replicate, and fed with a basal diet, or a basal diet supplemented with E. faecium (2.5 × 108 cfu/g feed). The experiment comprised two phases, consisting of the pre-salmonella challenged phase (from day 14 to day 21) and the post-salmonella challenged phase (from day 21 to day 42). At day 21 and day 22, the hens in SCON and SEF groups were orally challenged with 1.0 mL suspension of 109 cfu/mL S. Enteritidis (CVCC3377) daily, whereas the hens in CON and EF groups received the same volume of sterile PBS. Herein, our results showed that E. faecium administration significantly improved egg production and shell thickness during salmonella infection. Also, E. faecium affected host lipid metabolism parameters via downregulating the concentration of serum TG, inhibited oxidative stress and enhanced immune functions by downregulating the level of serum MDA and upregulating the level of serum IgG. Of note, E. faecium supplementation dramatically alleviated intestinal villi structure injury and crypt atrophy, and improved intestinal mucosal barrier injuries caused by S. Enteritidis challenge. Moreover, our data revealed that E. faecium supplementation ameliorated S. Enteritidis infection-induced the gut microbial dysbiosis by altering gut microbial composition (reducing Bacteroides, Desulfovibrio, Synergistes and Sutterella, and increasing Barnesiella, Butyricimonas, Bilophila and Candidatus_Soleaferrea), and modulating the gut microbial function, such as Cysteine and methionine metabolism, Pyruvate metabolism, Fatty acid metabolism, Tryptophan metabolism, Salmonella infection, and PI3K-Akt signaling pathway. Taken together, E. faecium has a strong capacity to inhibit S. Enteritidis colonization of hens. The results highlight the potential of E. faecium supplementation as a dietary supplement to combat S. Enteritidis infection in animal production and to promote food safety.